Information Aggregation and Adverse Selection - Aristotelis Boukouras; Kostas Koufopoulos (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2011)
We consider a general economy, where agents have private information about their types. Types can be multi-dimensional and potentially interdependent. We show that, if the interim distribution of types is common knowledge (the exact number of agents for each type is known), then a mechanism exists, which is consistent with truthful revelation of private information and which implements first-best allocations of resources as the unique Bayes-Nash equilibrium. Our result requires weak restrictions on preferences (Local Non-Common Indifference Property) and on the Pareto correspondence (Anonymity) and it is robust to small perturbations regarding the knowledge of the interim distribution. Our paper is useful in understanding the power of information aggregation in alleviating incentive constraints and is particularly pertinent to games with large populations, in which case the interim distribution of types converges to a unique distribution.
Keywords: D71; D82; D86; 330; adverse selection; anonymity; first-best allocations; full implementation; information aggregation; mechanism design; single-crossing property; Pareto correspondence